Clinical ontologies improve case finding of primary biliary cholangitis in UK primary and secondary care - Pericleous, M; Kelly, C; Odin, JA; Kallis, Y; McGee, C; Sherlock, J; Yonova, I; de Lusignan, S; Ala, A (Springer, 2020)
Introduction PBC registries in the UK focus on data from secondary care without clear coordinated contribution from primary care. The Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) receives data from > 500 primary care practices (PCPs). Notably, the Lancet commissioning group is extracting data from the RCGP RSC database to shape UK policy on liver disease. Aims To create a novel ontology to facilitate PBC case finding from primary care provider (PCP) records. Methods RCGP RSC data were collected from participating PCPs in the county of Surrey, UK. PBC diagnostic criteria of the AASLD and EASL guidelines were used to develop 725 data codes to facilitate patient record searches. A scoring system built into the ontology allowed categorization of cases as PBC definite, PBC probable, and PBC unlikely. Results A total of 218,099 records were searched from participating PCPs. Of these, there were 58 PBC definite, 2317 PBC probable, and 215,724 PBC unlikely patients. There were 32 PBC definite patients who did not match to our regional PBC database and were henceforth included as new-found cases. Two of these cases were not labeled as PBC by the PCP. From the PBC unlikely group, 7/215,724 (0.003%) patients were labeled as PBC in secondary care records; however, none of them were coded as having PBC by their PCPs. Conclusions Utilization of the UK National RCGP RSC database supported by novel ontology score has successfully helped us identify (i) new cases of PBC not known to local/regional secondary care providers and (ii) de novo PBC cases. There are many PBC probable cases whose data merit further careful evaluation.